Human T H 9 differentiation is dependent on signal transducer and activator of transcription (STAT) 3 to restrain STAT1-mediated inhibition - Zhang, Yuan; Siegel, Andrea M; Sun, Guangping; Dimaggio, Tom; Freeman, Alexandra F; Milner, Joshua D (Journal of allergy and clinical immunology, 2019)
Patients with loss-of-function (LOF) signal transducer and activator of transcription 3 (STAT3) mutations have dermatitis, enhanced IgE production despite a relative lack of immediate hypersensitivity, recurrent infection, and an increased rate of lymphoma in addition to a number of skeletal and connective tissue abnormalities. Patients with STAT1 gain-of-function (GOF) mutations also have susceptibility to candidiasis and sinopulmonary infection, as well as autoimmunity and squamous cell carcinoma, in addition to even more broad phenotypes. Because of the link between T 9 cells and allergic inflammation, autoimmunity, and antitumor surveillance and because evidence shows a role for either STAT3 or STAT1 in T 9 differentiation conflicts, we sought to determine the status on this lineage of STAT1 GOF and STAT3 LOF mutations in human subjects. We detected IL-9 levels and T 9 differentiation in patients with STAT3 LOF and STAT1 GOF mutations, together with T 9 transcript factors, and partially rescued their deficiency in vitro by adding cytokines they lacked or transfecting key molecules. We found that PBMCs or sorted naive CD4 T cells from patients with STAT3 LOF and STAT1 GOF mutations had impaired T 9 generation/differentiation. STAT3 inhibition in normal T 9 cultures diminished early IL-21 induction and late IL-9 production, whereas exogenous IL-21 enhanced T 9 differentiation, even with STAT3 inhibition, by restoring suppressor of cytokine signaling 3 expression and thus inhibiting excessive phosphorylated signal transducer and activator of transcription (p-STAT) 1 activation. Furthermore, exogenous expression of suppressor of cytokine signaling 3 or either T-bet or STAT1 RNA interference in STAT3 LOF cells partially rescued IL-9 differentiation. Collectively, these results suggest that human T 9 differentiation depends on normal p-STAT3 and IL-21 production to suppress p-STAT1 activation and T-bet transcription.